Possible routes and transmission control of COVID-19 in the practice of collective water sports: Optimization of sanitation measures in the contemporary city in times of pandemic - Faria, Fábio Henrique; Soares, Alexandra Fátima Saraiva; Battistelle, Rosane Aparecida Gomes (Technical and Scientific Journal Green Cities, 2021)
Global urban management was affected by the COVID-19 pandemic. Thus, this work aims to analyze possible routes of transmission of SARSCoV-2 in one of the activities of society, during the water sports practice and discussed the control measures of COVID-19 established in some national and international health protocols linked to the insertion of interventions in the city to promote the development of aquatic activities. This is an exploratory research to review the technical literature to present the current state of knowledge regarding the occurrence, persistence, possibility of transmission of SARS CoV-2 during the practice of collective water sports. Relevant security protocols were analyzed, regarding their functionalities and assumptions. It has been found that, to date, there is no scientific evidence that transmission can occur within swimming pools through contact with treated water. The protocols and studies analyzed emphasize concerns related to the airways, constituting the transmission route with the highest rate of contamination through respiratory droplets, as well as contact with contaminated surfaces. As a way of controlling the transmission of the new coronavirus, it is necessary to avoid close contact and without facial protection, agglomerations and places with poor ventilation. The research confirmed the hypothesis that the current preventive measures established in the health protocols to mitigate the spread of COVID-19, during sports and collective practice in aquatic environments, if known and observed, are sufficient to prevent the transmission of the disease in these environments. KEYWORDS: Smart and Sustainable Cities. COVID-19. Water sport.